MENEGUHKAN KESADARAN GENDER MAHASISWI Potret Kajian Kitab Al-Mar’ah Bayna Asy-Syarah Wa Al-Ḥaya di Yayasan Fahmina Cirebon - lufaefi lufaefi (PSGA LP2M IAIN Pontianak, 2020)
Discrimination against women, both in the social sphere and in the teaching source literature, still occurs in many places. This has an impact on gender inequality in the community, even in Islamic boarding schools. The Al-Mar'ah Bayna Asna-Syarah Wa Al-Ḥaya Study Program is present at the Fahmina Cirebon Foundation to foster a more progressive gender awareness. The method used in this study is a qualitative method using three ways in data collection, namely observation, interviews and documentation. This research shows that the program that is raised by KH. Hussein Muhammad as the speaker of book study was quite successful. The study of the book Al-Marah bayna Asy-Syarah Wal Ḥaya can foster gender fair awareness of female students. ¬The number of women present is more dominant than men. From the cognitive, affective and psychomotor aspects, it can be seen the results of female students' catch ability, namely by asking questions, criticizing and understanding the gender material delivered. In the affective domain, female students benefit from the study of the book. Whereas in the psychomotor domain, there are female students who apply gender awareness by socializing lessons about gender.